The Untouchable Ventral Nucleus of the Trapezoid Body: Preservation of a Nucleus in an Animal Model of Autism Spectrum Disorder - Mansour, Yusra; Kulesza, Randy J. (Frontiers in Integrative Neuroscience, 2021)
Autism spectrum disorder (ASD) is a neurodevelopmental condition characterized by repetitive behaviors, poor social skills, and difficulties with communication and hearing. The hearing deficits in ASD range from deafness to extreme sensitivity to routine environmental sounds. Previous research from our lab has shown drastic hypoplasia in the superior olivary complex (SOC) in both human cases of ASD and in an animal model of autism. However, in our study of the human SOC, we failed to find any changes in the total number of neurons in the ventral nucleus of the trapezoid body (VNTB) or any changes in cell body size or shape. Similarly, in animals prenatally exposed to the antiepileptic valproic acid (VPA), we failed to find any changes in the total number, size or shape of VNTB neurons. Based on these findings, we hypothesized that the neurotransmitter profiles, ascending and descending axonal projections of the VNTB are also preserved in these neurodevelopmental conditions. We investigated this hypothesis using a combination of immunohistochemistry and retrograde tract tracing. We found no difference between control and VPA-exposed animals in the number of VNTB neurons immunoreactive for choline acetyltransferase (ChAT). Additionally, we investigated the ascending projections from the VNTB to both the central nucleus of the inferior colliculus (CNIC) and medial geniculate (MG) and descending projections to the cochlea. Our results indicate no significant differences in the ascending and descending projections from the VNTB between control and VPA-exposed animals despite drastic changes in these projections from surrounding nuclei. These findings provide evidence that certain neuronal populations and circuits may be protected against the effects of neurodevelopmental disorders.